Development of Dapagliflozin Solid Lipid Nanoparticles as a Novel Carrier for Oral Delivery: Statistical Design, Optimization, In-Vitro and In-Vivo Characterization, and Evaluation - Aziz Unnisa; Ananda K. Chettupalli; Turki Al Hagbani; Mohammad Khalid; Suresh B. Jandrajupalli; Swarnalatha Chandolu; Talib Hussain (MDPI AG, 2022)
Controlling hyperglycemia and avoiding glucose reabsorption are significant goals in type 2 diabetes treatments. Among the numerous modes of medication administration, the oral route is the most common. Introduction: Dapagliflozin is an oral hypoglycemic agent and a powerful, competitive, reversible, highly selective, and orally active human SGLT2 inhibitor. Dapagliflozin-loaded solid lipid nanoparticles (SLNs) are the focus of our present investigation. Controlled-release lipid nanocarriers were formulated by integrating them into lipid nanocarriers. The nanoparticle size and lipid utilized for formulation help to regulate the release of pharmaceuticals over some time. Dapagliflozin-loaded nanoparticles were formulated by hot homogenization followed by ultra-sonication. The morphology and physicochemical properties of dapagliflozin-SLNs have been characterized using various techniques. The optimized dapagliflozin-SLNs have a particle size ranging from 100.13 ± 7.2 to 399.08 ± 2.4 nm with 68.26 ± 0.2 to 94.46 ± 0.7% entrapment efficiency (%EE). Dapagliflozin-SLNs were optimized using a three-factor, three-level Box-Behnken design (BBD). Polymer concentration (X1), surfactant concentration (X2), and stirring duration (X3) were chosen as independent factors, whereas %EE, cumulative drug release (%CDR), and particle size were selected as dependent variables. Interactions between drug substances and polymers were studied using Fourier transform infrared spectroscopy (FTIR) and scanning electron microscopy (SEM). Differential scanning calorimetry (DSC), X-ray diffraction (XRD), and atomic force microscopy (AFM) analysis indicated the crystalline change from the drug to the amorphous crystal. Electron microscope studies revealed that the SLNs' structure is nearly perfectly round. It is evident from the findings that dapagliflozin-SLNs could lower elevated blood glucose levels to normal in STZ-induced diabetic rats, demonstrating a better hypoglycemic impact on type 2 diabetic patients. The in vivo pharmacokinetic parameters of SLNs exhibited a significant rise in Cmax (1258.37 ± 1.21 mcg/mL), AUC (5247.04 mcg/mL), and oral absorption (2-fold) of the drug compared to the marketed formulation in the Sprague Dawley rats.